2016
DOI: 10.1111/ped.13176
|View full text |Cite
|
Sign up to set email alerts
|

Maternal zinc deficiency and congenital anomalies in newborns

Abstract: There is an association between congenital malformation in newborns and maternal zinc deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Sever and Emmanuel 24 claimed that maternal zinc deficiency was related to congenital malformations of the central nervous system. Moghimi et al 25 conducted a case–control study in Iran involving mothers of 80 neonates with congenital anomalies. They also found an association between congenital malformation in newborns and maternal zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Sever and Emmanuel 24 claimed that maternal zinc deficiency was related to congenital malformations of the central nervous system. Moghimi et al 25 conducted a case–control study in Iran involving mothers of 80 neonates with congenital anomalies. They also found an association between congenital malformation in newborns and maternal zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, zinc content was restored after zinc supplementation in the maternal diet. It has been reported that zinc deficiency during pregnancy is associated with increased risks of fetal malformation, including neural tube defects (Moghimi et al, 2017;Brion et al, 2021). Previous animal studies reported that prenatal caffeine consumption could induce altered sleep and locomotion, anxiety, and learning abilities, in addition, it may interfere with brain zinc absorption (Cortés-Albornoz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with what is observed in humans, as maternal Zn deficiency during pregnancy in humans increases the risk of fetal growth restriction [70], with a clear association between maternal Zn level during pregnancy and the risks of low birth weight and small gestation age infants (Figure 2). Additional studies on human populations have confirmed the effect of maternal Zn deficiency on growth retardation [71,72], but have also uncovered congenital abnormalities [73], immune system failures [74,75], reproductive defects [76,77], and more generally an increased susceptibility to complex pathologies [46,47]. Unfortunately, studies conducted on humans are intrinsically descriptive and those focusing on molecular impact of Zn on development are rare.…”
Section: Impact Of Zn Deficiency On Early Embryonic Developmentmentioning
confidence: 99%